FREQUENCY OF LOW BACK PAIN AND ITS IMPACT ON MEDICAL STUDENTS OF BILAWAL MEDICAL COLLEGE: A RETROSPECTIVE SURVEY - BALOCH , S; DURANI , W; DURANI , RZ; ALI , Z; RIYYAN , M; CHANIA , HA; SAJID , S; FATIMA , M; KUMAR , S; ALI , B; LAGHARI , F; LAGHARI , A; et al. (Biological and Clinical Sciences Research Journal, 2024)
Low back pain (LBP) is a significant health and economic problem among populations in high-resource countries. LBP is one of the prevalent complaints among all age groups. Objective: To assess the frequency of low back pain (LBP) among medical and its impact on their daily activities and life while exploring potential associations with socio-demographic factors, exercise habits, pain-relieving consumption, history of spine trauma, and body mass index (BMI) Methods: A retrospective survey was conducted at Bilawal Medical College (BMC) among first year to final year MBBS students. Data was collected during the period of January 2022 to February 2023 using a questionnaire created on Google Form that included questions regarding the information on socio-demographic characteristics and factors such as exercise, pain-relieving consumption, any history of spine trauma, specific questions pertaining to LBP pain frequency and issues. Results: A total of 62 medical students participated in the study, of which about half were in their fourth year (50.0%), followed by the third year (20.9%) of medical school. The 20–24 age group accounted for most individuals (64.5%), followed by the 25–30-year-old age group (33.9%). Only 25.8% of the participants were overweight, defined as having a BMI of more than 25 kg/m2. Conclusion: It was concluded that low back pain is one of the most frequent health crises among medical students. Students from senior academic years reported more frequent lower back pain, which was highly significant due to increased mental stress and increased physical strain due to clinical learning. Additionally, it was found that there is no potential link between BMI and a history of spine trauma on the frequency of lower back pain or its impact on the medical student’s life and their daily activities.